Psychophysical and neuroimaging responses to moving stimuli in a patient with the Riddoch phenomenon due to bilateral visual cortex lesions. (May 2019) - Arcaro, Michael J.; Thaler, Lore; Quinlan, Derek J.; Monaco, Simona; Khan, Sarah; Valyear, Kenneth F.; Goebel, Rainer; Dutton, Gordon N.; Goodale, Melvyn A.; Kastner, Sabine; Culham, Jody C.
Abstract: Patients with injury to early visual cortex or its inputs can display the Riddoch phenomenon: preserved awareness for moving but not stationary stimuli. We provide a detailed case report of a patient with the Riddoch phenomenon, MC. MC has extensive bilateral lesions to occipitotemporal cortex that include most early visual cortex and complete blindness in visual field perimetry testing with static targets. Nevertheless, she shows a remarkably robust preserved ability to perceive motion, enabling her to navigate through cluttered environments and perform actions like catching moving balls. Comparisons of MC's structural magnetic resonance imaging (MRI) data to a probabilistic atlas based on controls reveals that MC's lesions encompass the posterior, lateral, and ventral early visual cortex bilaterally (V1, V2, V3A/B, LO1/2, TO1/2, hV4 and VO1 in both hemispheres) as well as more extensive damage to right parietal (inferior parietal lobule) and left ventral occipitotemporal cortex (VO1, PHC1/2). She shows some sparing of anterior occipital cortex, which may account for her ability to see moving targets beyond 15 degrees eccentricity during perimetry. Most strikingly, functional and structural MRI revealed robust and reliable spared functionality of the middle temporal motion complex (MT+) bilaterally. Moreover, consistent with her preserved ability to discriminate motion direction in psychophysical testing, MC also shows direction-selective adaptation in MT+. A variety of tests did not enable us to discern whether input to MT+ was driven by her spared anterior occipital cortex or subcortical inputs. Nevertheless, MC shows rich motion perception despite profoundly impaired static and form vision, combined with clear preservation of activation in MT+, thus supporting the role of MT+ in the Riddoch phenomenon. Highlights: Patient MC can perceive moving but not static targets (Riddoch phenomenon). MC shows activation in area MT+ despite extensive bilateral occipital lesions. MC discriminates motion direction and shows direction-selective adaptation in MT+.